The prevention priority: linking education and homelessness data to inform policy and practice - Mackie, Peter; Thomas, Ian (International Journal of Population Data Science, 2019)
Childhood and youth homelessness is a seemingly intractable problem across the globe. Yet, the paradigm shift in homelessness policy towards prevention is raising new questions and new opportunities for researchers, policy makers, and practitioners; specifically, schools as sites for early intervention. The aim of this paper is to shed new light on the potential power of data linkage in both understanding the relationship between homelessness and education (particularly attainment) and in guiding prevention policy and practice. Significantly, the paper draws on data from two separate projects exploring the links between youth homelessness and education – each using a different methodology for data linkage, hence the paper offers both methodological and practical insight. The first project has sought to understand educational achievement of homeless children by linking local authority administrative homelessness data with national education data in Wales. The key methodological challenge here has been that the homelessness data only relate to the main applicant for homelessness assistance, so other administrative data sources have had to be drawn on to identify young people living in homeless households. Early findings suggest young people experiencing homelessness attain below average in school, but the key lesson here is largely methodological. The second part of the paper focuses on identifying which schools homeless young people have attended – with the aim of informing future interventions in these schools and providing a baseline for monitoring their impacts. The methodology differs markedly from the first project and is based upon local authority homelessness and education departments sharing data and undertaking linkage within the authority. This method proves to be highly effective in matching nearly all young people and not only identifying schools but also other key experiences of the young people (e.g. having been in care). The conclusion of the paper is that data linkage, at different scales, i.e. national infrastructure vs local linkage, offer different pathways through which knowledge can influence practice.